Research of the Dynamics Performance and Modification of Helical Gear in Marine - Xuezhi Li; Meng Chen (Jixie chuandong)
Aiming at the problem of the helical gears meshing which lead to the fatigue damage and shock of the gear surface， the dynamic performance and modification are analyzed and studied. The dynamics model of helical gears meshing is built based on the impact is affected by the backlash. The coupled model of rigid and flexible is built by Adams， and the angular velocity and load torque of the gear are obtained. Then， the finite element model of helical gear is established， the position and the curve of the maximum contact stress of are obtained. Finally， the angular acceleration， load torque and stress variation curve of the driven gear after modification are obtained by using the arc modification method. The research results indicate that the contact strength is improved based on the short-modification， which can provide the basis for gears analysis， such as， the fatigue life and the transmission efficiency.